2003
DOI: 10.1023/a:1024601906942
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This paper reports a test of the efficacy of Familias Unidas, a Hispanic-specific, ecologically focused, parent-centered preventive intervention, in promoting protection against and reducing risk for adolescent behavior problems. Specifically, the intervention was designed to foster parental investment, reduce adolescent behavior problems, and promote adolescent school bonding/academic achievement, all protective factors against drug abuse and delinquency. One-hundred sixty seven Hispanic families of 6th and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(87 citation statements)
references
References 22 publications
1
86
0
Order By: Relevance
“…A general conclusion that can be derived from the present results is that skills and processes that are associated with the specific activities conducted in the intervention sessions, such as generating alternatives with critical problem solving and personal expressiveness with experiential focusing, may be most amenable to change by those strategies. These results are consistent with previous observations that effects detected in intervention studies are generally limited to indices that are directly targeted in the intervention activities (e.g., Ialongo et al, 1999;Pantin et al, 2003).…”
Section: The Specificity Of Intervention Effectssupporting
confidence: 92%
“…A general conclusion that can be derived from the present results is that skills and processes that are associated with the specific activities conducted in the intervention sessions, such as generating alternatives with critical problem solving and personal expressiveness with experiential focusing, may be most amenable to change by those strategies. These results are consistent with previous observations that effects detected in intervention studies are generally limited to indices that are directly targeted in the intervention activities (e.g., Ialongo et al, 1999;Pantin et al, 2003).…”
Section: The Specificity Of Intervention Effectssupporting
confidence: 92%
“…Instead, culturally relevant interventions for Latino immigrant parents should facilitate a group learning experience that promotes trust, social support, and empowerment. Previous research has confirmed the value of facilitating parental social support networks, as they assist parents in acquiring community resources which help them overcome contextual challenges (Pantin et al, 2003). …”
Section: Discussionmentioning
confidence: 93%
“…Thus, research results confirm previous findings related to parent training with Latino populations. In particular, it is important to inform interventions according to relevant Latino cultural values, there is a need to inform parent training based on collaborative approaches, and interventions should be designed to accommodate members of the extended family (Castro et al, 2006; Pantin et al, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…Reviews of such interventions indicate that in addition to addressing risk/protective factors such as knowledge, social norms, and social influence, most efficacious programs focus on improving family environment (e.g., cohesion) and/or parenting practices (e.g., parental monitoring, parent-adolescent communication) (Prado, Szapocznik, Maldonado-Molina, Schwartz, & Pantin, 2008; Szapocznik, Prado, Burlew, Williams, & Santisteban, 2007; Castro et al, 2006). Programs such as Familias Unidas (Pantin et al, 2003), Neustras Familias (Martinez & Eddy, 2005), Keepin’ it REAL (Marsiglia & Hecht, 2005), and Family Effectiveness Training program (FET; Szapocznik et al, 1989) attempt to promote protective factors related to traditional Hispanic values such as familism, respect for elders, and ethnic pride. To some extent, these programs are guided by the assumption that among Hispanic families, acculturation to the U.S. is related to the erosion of traditional collectivistic values and mores (Prado et al, 2008).…”
Section: Discussionmentioning
confidence: 99%